FACTORS INFLUENCING THE USE OF CHATGPT TO DRIVE BUSINESS PERFORMANCE: A CASE STUDY OF TRAVEL INSURANCE - Saengmahachai , Araya (Journal of MCU Nakhondhat, 2025)
This research aims to investigate the factors influencing attitudes toward using of ChatGPT in the travel insurance industry, focusing on insurance agents and policyholders. It further explores the relationship between attitudes and usage behavior, and examines the impact of ChatGPT usage behavior on individual users’ perceived work performance. The conceptual framework is grounded in Everett Rogers' Diffusion of Innovation Theory, which identifies four key characteristics of innovation: compatibility, complexity, trialability, and observability. These dimensions analyze their influence on users’ attitudes, usage behaviors, and perceived work performance within each group. Data were collected via an online questionnaire from 589 participants, comprising insurance agents and buyers. The data were analyzed using multiple regression analysis. The findings are consistent with the research objectives. Specifically, the innovation characteristics compatibility, complexity, trialability, and observability were found to significantly influence positive attitudes toward ChatGPT in the context of the travel insurance business. Positive attitudes, in turn, led to appropriate and sustained usage behaviors, which subsequently affected users’ perceptions of their work performance. The study also revealed significant differences between insurance agents and policyholders regarding their perceptions and usage behaviors of ChatGPT. These findings provide valuable insights for developing and promoting of adequate and appropriate applications of AI technologies within the travel insurance industry.